The Impact of Marketing Concept on Customer Patronage in United Bank for Africa Plc in Delta State - Temu, Clement; Joy, Oderoha Omogor (Universitas Kuningan, 2025)
This study investigates the impact of the marketing concept on customer patronage in United Bank for Africa (UBA) Plc in Delta State. Specifically, it explores the roles of three key variables: the application of the marketing concept, customer satisfaction, and customer-centric marketing strategies. Using a regression analysis of data collected from 327 respondents, the findings reveal that all three variables have a statistically significant influence on customer patronage and loyalty. Firstly, the application of the marketing concept was shown to positively affect customer patronage. UBA’s strategies, such as tailoring services to customer needs, offering innovative products, and focusing on customer satisfaction, have proven effective in attracting and retaining customers. Secondly, customer satisfaction emerged as a critical determinant of customer patronage, emphasizing that satisfied customers are more likely to remain loyal and recommend the bank to others. Lastly, customer-centric marketing strategies, including loyalty programs and personalized services, were identified as significant drivers of customer loyalty, fostering long-term relationships and enhancing customer retention. These findings underscore the importance of strategic marketing practices in building strong customer relationships within the banking sector. The study concludes that UBA’s marketing efforts centered around customer-focused approaches are effective in driving patronage and loyalty. Recommendations include strengthening the marketing concept, enhancing customer satisfaction through service improvements, expanding loyalty programs, and leveraging digital technologies for better customer engagement. The insights provide valuable lessons for banks and organizations seeking to sustain growth in a competitive financial industry.